2008
DOI: 10.1080/10410230802056388
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Canadian Aboriginal Online Health Care Forums

Abstract: Internet-based discussion forums provide access to health information and social support, and serve as a resource for others. This investigation analyzed health-oriented Aboriginal Internet discussion forum (Forum A; Forum B) conversations. The findings were framed with Nutbeam's model of health literacy. Discussions within Forum B were centralized around issues of political activism and advocacy regarding Aboriginal health care. Activity in Forum A encouraged the development of "virtual" social capital, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Some health forums are moderated by health professionals whereas others are not. Numerous reports have focused on content analysis and description of forum topics, user demographic characteristics, the conversations or activities occurring and the health literacy skills of the forum participants [9,12]. Little is known, however, about the accuracy of information provided on unmoderated health forum sites.…”
Section: Introductionmentioning
confidence: 97%
“…Some health forums are moderated by health professionals whereas others are not. Numerous reports have focused on content analysis and description of forum topics, user demographic characteristics, the conversations or activities occurring and the health literacy skills of the forum participants [9,12]. Little is known, however, about the accuracy of information provided on unmoderated health forum sites.…”
Section: Introductionmentioning
confidence: 97%
“…Alternatively, prostate cancer patients found that participating in a self help group served as a significant and reliable source of emotional support, experiential cancer care information and of additional medical information [10]. Advances in information technology within the past few decades have created innovative strategies for accessing information, social support and political advocacy within a health context [11,12]. The availability of cancer care information, including that available online, has assisted patients in developing a sense of control, reducing anxiety, promoting self care and generating a sense of security and safety [7].…”
Section: Introductionmentioning
confidence: 98%
“…usenet and bulletin board systems), including psychosocial (e.g. decreasing stress Sharf, ; Braithwaite et al ., ; Monnier et al ., ; Maloney‐Krichmar and Preece, ; Im and Chee, ; Donelle and Hoffman‐Goetz, ; Eichhorn, ; Ginossar, ; Macias and McMillan, ) and instrumental benefits (e.g. 24‐hour availability and anonymity) (Cline and Haynes, ).…”
Section: Introductionmentioning
confidence: 99%